Evaluation of Different Phenotypic and Genotypic Methods for Detection of Methicillin Resistant Staphylococcus aureus ( MRSA) - Koupahi, Hossein; Honarmand Jahromy, Sahar; Rahbar, Mohammad (Iranian journal of pathology, 2016)
Methicillin resistant (MRSA) has been emerged as a nosocomial and community acquired pathogen worldwide. There are many challenges for laboratory detection of MRSA. The aim of this study was to compare different phenotypic methods with PCR based method as a gold standard for detection of gene. A total of 220 clinical isolates of which were isolated from various clinical specimens from September 2013 until the June of 2014 in Milad Hospital of Tehran, Iran was subject of our study. Methicillin resistance was determined by oxacillin and cefoxitin disks, oxacillin screen agar and CHROMagar™ MRSA medium. The results of these methods were compared with gene based PCR method as a gold standard method. Among 220 isolates from , 105 (47.72%) isolates were positive for gene by PCR method. The results of cefoxitin disk diffusion method with 100% sensitivity and specificity was the same as PCR method .CHROMagar™ MRSA medium had 98.13% sensitivity and 100% specificity. Oxacillin disk diffusion and oxacillin screen agar had 95.42% and 97.22% sensitivity respectively. Result of cefoxitin disk diffusion method with 100% sensitivity and specificity was the same as PCR method for detection gene. Cefoxitin disk diffusion method can be used as an alternative method of PCR for detection of MRSA.